Czytanie, pisanie, praca przy komputerze lub oglądanie telewizji a krótkowzroczność - Czepita, Damian; Mojsa, Artur; Ustianowska, Maria; Czepita, Maciej; Lachowicz, Ewelina (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: The aim of our study was to investigate on a large population if reading, writing, working on a computer or watching television might be associated with the occurrence of myopia. Material and methods: A total of 5865 schoolchildren were examined (2792 boys and 3073 girls, at the age 6-18 years, mean age 11.9, S.D. 3.3). The examination included retinoscopy under cycloplegia induced with 1% tropicamide. Myopia was defined as a spherical equivalent of at least -0.50 dioptres. Mean refractive error was -1.2, SD 1.3. (The students and their parents completed a questionnaire on the child’s visual work. Data analysis was performed using independence chi-squared Pearson test; p-values of <0.05 were considered statistically significant. Results: It was observed that myopia occurs more often in students who read and write >2 hours/ day (p<0.001), and also work >0.8 hours/ day on a computer (p<0.01). Furthermore, no increase in the prevalence of myopia in subjects who spend >2 hours/ day watching television was found (p>0.05). Conclusions: The obtained results indicate that reading, writing, working on a computer might be associated with the occurrence of myopia among schoolchildren. Watching television is not related to the occurrence of myopia.